2003
DOI: 10.1002/jctb.859
|View full text |Cite
|
Sign up to set email alerts
|

Lipase production in continuous culture of Candida rugosa

Abstract: The yeast Candida rugosa produces multiple extracellular lipases. The production of extra-and intracellular lipases was investigated in continuous cultures using a sole or different mixtures of carbon sources. Also, the effect of different C:N ratios was tested. Lipase productivity in continuous cultures increased by 50% compared with data obtained from batch fermentations and depended on the dilution rate applied. Maximum yields relative to consumed substrate were obtained with oleic acid at low dilution rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
3
12
1
Order By: Relevance
“…In the present study, the simultaneous increase of carbon and nitrogen concentrations notably increased lipase yield (Lip max = 2.50 IU/ml). In accordance with our findings, Montesinos et al (2003) studying the effect of nitrogen limitation upon lipase secretion by Candida rugosa ATCC found that Lip secretion was almost completely suppressed in nitrogenlimited media. Pereira-Meirelles et al (1997) reported maximum lipase concentrations around 2.5-3.0 IU/ml by a wild C. lipolytica strain cultivated on media containing olive oil and peptone, while higher quantities of total (extra-cellular and cell-bound) lipase were obtained in media enriched with both yeast extract and peptone (5.0-8.5 IU/ml) (Pereira-Meirelles et al 2000).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the simultaneous increase of carbon and nitrogen concentrations notably increased lipase yield (Lip max = 2.50 IU/ml). In accordance with our findings, Montesinos et al (2003) studying the effect of nitrogen limitation upon lipase secretion by Candida rugosa ATCC found that Lip secretion was almost completely suppressed in nitrogenlimited media. Pereira-Meirelles et al (1997) reported maximum lipase concentrations around 2.5-3.0 IU/ml by a wild C. lipolytica strain cultivated on media containing olive oil and peptone, while higher quantities of total (extra-cellular and cell-bound) lipase were obtained in media enriched with both yeast extract and peptone (5.0-8.5 IU/ml) (Pereira-Meirelles et al 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Results for other wild Candida species showed a lipase production of the same magnitude with the present investigation (e.g. concentrations 2-15 IU/ml for various carbon sources used) (Dalmau et al 2000;Montesinos et al 2003). In order to obtain increased lipase production by Y. lipolytica strains, combinations of genetic engineering and mutagenesis methods have been employed.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…), while their production is also substantially enhanced by the addition of organic nitrogen (e.g., peptone, urea, etc.) to the culture medium [66,83,84,[86][87][88][89]. In the submerged cultures carried out with stearin utilized as the sole substrate by the strain ACA-DC 50109, extracellular lipase was secreted into the medium in non-negligible amounts; lipase quantities were detected in the culture medium regardless of the substrate fat or the nitrogen concentration, and secretion occurred during primary anabolic activity [40].…”
Section: Introductionmentioning
confidence: 99%
“…However, a considerable amount of the research carried out to date has focused on small-scale procedures, while less information is available on the particular characteristics of lipolytic enzyme biosynthesis in bioreactors and the feasibility of diverse culture modes, such as batch, fed-batch, or continuous systems [6][7][8]. Over the last few months, research concerning lipase production by yeasts and fungi in bioreactors has been employed to obtain high levels of lipase production, thus demonstrating the interest that the scale-up of this kind of biological process is triggering nowadays and then encouraging further research in this field [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%